Sill-related seafloor domes in the Zhongjiannan Basin, western South China Sea. (December 2020) - Geng, Minghui; Song, Haibin; Guan, Yongxian; Chen, Jiangxin; Zhang, Ruwei; Zhang, Baojin; Zhang, Xudong
Abstract: Magmatism can exert significant impact on sedimentary basins such as the Zhongjiannan Basin (ZJNB), western South China Sea. We have evaluated multibeam bathymetric and multichannel seismic reflection data acquired by the Guangzhou Marine Geological Survey in recent years, in order to investigate the distribution, the characteristics and the subsurface structures related to seafloor domes found in the northeastern ZJNB. Our data revealed forty-two domes at water depths between 2312 m and 2870 m, which are clustered around volcanic mounds, large seamounts and along the edge of the central depression in the study area. These domes are generally circular to elongate or irregular in plan view with large basal areas, and they also have gentler flanks (dips of 1.46°–7.73°) with vertical reliefs ranging from tens to hundreds of meters. In seismic sections, majority of the domes are underlain by variably shaped and complex magmatic sills, which provide a cause-effect relationship between domes formation and igneous intrusions. These intrusions heat surrounding organic-rich sediments, release hydrocarbons, fluidize sediment pore waters and form gas-rich fluids, which fill in sediment and uplift overlying strata immediately above the sills to form forced folds, which are manifested as seafloor domes. These sill-folds-dome structures have important implications for understanding geomorphologic features caused by sills emplaced at depth. Highlights: First insight of sill-folds-dome structures in the western South China Sea. Identification and characterization of forty-two domes in the northeastern Zhongjiannan Basin. Correlation of seafloor domes with subsurface forced folds and igneous intrusions.